(untitled) (International Conference on Computers in Education, 2022)
This paper discusses the connotation and significance of blended training and introduces the process of implementing blended training. This paper elaborates the case of implementing blended training, and finds out the highlights, advantages and challenges of blended training through the case. Finally, it discusses how to implement blended training in on-the-job training to realize the combination of online and offline